PEMBERDAYAAN MASYARAKAT OLEH KELOMPOK TANI GEMAH RIPAH DALAM PENGOLAHAN PRODUK BAYAM BRAZIL DI KELURAHAN BAUSASRAN KOTA YOGYAKARTA - Loi, Andi Julyanto; Sulistiya, Sulistiya; Hariadi, Untoro (Agros Journal of Agriculture Science, 2023)
The purpose of this research was to identify how benefits of community empowerment obtained from the use of Brazilian Spinach carried out by Kelompok tani Gemah Ripah in Bausasran Village; This was a Qualitative research with descriptive analysis desain of study. Data was aqquired from 11-14 informants who were dominated the conditions. The research location was determined as purposively based on primary data criteria regarding Brazilian spinach by the Kelompok tani Gemah Ripah as Farmers Group in Bausasran Village, Danurejan District, Yogyakarta City. The informants are residents or communities involved in the group as Kelompok tani Gemah Ripah. The informants within were selected by Purposive Sampling and Snowball Sampling methods. As to generated the data was reducted using the Narrative-Descriptive Analyze Section; The research result shows that Kelompok tani Gemah Ripah is affordable to empower the community through processing Brazilian spinach products with relevant benefits in the form of strengthening community potential, breaks out the business opportunities, brings on a tourist attarction as agrotourism, careers opportunities and collaboration. Keywords: Community Empowerment; Kelompok Tani Gemah Ripah; Brazillian Spinach INTISARIPenelitian ini dilakukan untuk mengetahui: “Manfaat pemberdayaan masyarakat yang diperoleh dari pemanfaatan bayam brazil yang dilakukan oleh Kelompok tani Gemah Ripah di Kelurahan Bausasran”. Metode dasar yang digunakan dalam penelitian ini adalah metode analisis deskriptif. Lokasi penelitian ditentukan secara Purposive berdasarkan kriteria data primer tentang bayam Brazil oleh Kelompok tani Gemah Ripah di Kelurahan Bausasran, Kecamatan Danurejan, Kota Yogyakarta. Informan merupakan warga atau masyarakat yang terlibat dalam Kelompok tani Gemah Ripah. Informan dipilih dengan metode Purposive Sampling dan Snowball Sampling diambil sebanyak 11-14 orang informan. Data analisis dengan cara Descriptive Naratif; Hasil penelitian menunjukkan bahwa Kelompok tani Gemah Ripah mampu memberdayaan masyarakat melalui pengolahan produk bayam brazil dengan manfaat yang relevan berupa kemapanan potensi, mandiri menciptakan peluang usaha, menciptakan destinasi wisata, menciptakan karir dan kerjasama. Kata Kunci: Pemberdayaan Masyarakat, Kelompok tani Gemah Ripah, Bayam Brazil